Abiotic and Biotic Determinants of Plant Diversity in Aquatic Communities Invaded by Water Hyacinth [Eichhorniacrassipes (Mart.) Solms] - Wu, Hao; Ding, Jianqing (Frontiers in Plant Science, 2020)
Rapid global environmental changes could exacerbate the impacts of invasive plants on indigenous plant diversity, especially for freshwater ecosystems characterized by relatively simple plant community structures with low bioresistance. However, the abiotic and biotic determinants of plant diversity in aquatic invaded habitats remain unclear. In this study, we measured four α-species diversity indices (the Patrick richness index, Shannon-Wiener diversity index, Simpson diversity index and Pielou evenness index) in aquatic plant communities invaded by Eichhornia crassipes in southern China. We also recorded eight environmental parameters of these communities (longitude, latitude, elevation, dissolved oxygen, water conductivity, nitrate nitrogen, temperature and precipitation), together with nine biotic traits of E. crassipes (abundance, invasion cover, height, total carbon (C) content of the leaves and stems, total nitrogen (N) content of the leaves and stems, and the C:N ratio of leaves and stems). We then used regression analysis and redundancy analysis (RDA) to determine the dominant factors related to plant diversity. We found that the environment significantly affected E. crassipes abundance, height, coverage, stem carbon and tissue nitrogen, while the leaf C:N stoichiometric ratio was relatively stable. Increasing longitude significantly increased plant diversity, while elevated dissolved oxygen and precipitation slightly improved plant diversity, but increased elevation caused negative effects. E. crassipes invasion significantly decreased all four diversity indices. Increases in E. crassipes coverage and leaf C:N strongly decreased plant diversity, and increased abundance slightly decreased diversity. Our study indicates that both the changing water environment and the properties of the aquatic invasive plants could have significant impacts on plant diversity. Thus, more attentions should be paid to aquatic invasion assessment in lower longitudinal regions with lower native hydrophyte diversity.